Child-Friendly City Model Based on Collaborative Governance in Depok City, Indonesia - Ella Lesmanawaty' Wargadinata (Institut Pemerintahan Dalam Negeri, 2025)
Despite the adverse impacts of Jakarta's rapid development as the national capital, Depok City must ensure a safe and supportive environment for particularly vulnerable children in need of protection. As a fundamental asset to the city's future, children play a critical role in its long-term development.This study explores a collaborative governance model on a Depok Child-Friendly City model. The paper employs a qualitative research approach; data were collected through field observations, in-depth interviews with key stakeholders, and analysis of secondary sources, including policy documents, regulations, and prior research. The findings reveal that, despite the constraints posed by rapid urbanization, implementing the Child-Friendly City program in Depok continues to progress. The initiatives primarily attributed to fulfilling critical collaboration prerequisites, including the active involvement of multi-level government actors, the private sector, community organizations, and academic institutions. These stakeholders contribute through contextual understanding, shared commitment, and aligning responsibilities and visions based on their respective capacities and authorities. The study concludes that such a multi-stakeholder collaboration model is instrumental in promoting an urban environment conducive to children's growth and development.